Compression molding method of long fiber composite material loading wheel for vehicle tire

Through the molding method of long fiber composite materials, the shortcomings in strength, toughness and mass production of existing automotive tire weight-bearing wheels are solved, and high-strength, high-toughness and mass-produced loading wheels are achieved, meeting the harsh working conditions of armored vehicles.

CN119840202AInactive Publication Date: 2025-04-18LAIZHOU JINTIAN MACHINERY
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202510316156.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing automotive tire load wheels have shortcomings in weight, mechanical processing, mass production and performance under harsh working conditions, especially the product accuracy is poor, the fiber layer bonding force is weak, and it is difficult to meet the needs of armored vehicles.

Method used

The molding method of long fiber composite materials is adopted, and the load bearing wheels with high strength and toughness are prepared by combining the continuous fiber bundle with the resin liquid, and cutting, laying, hot pressing and demolding steps such as prepreg.

Benefits of technology

It realizes the high strength, high toughness and difficult to layer the load-bearing wheel, which is suitable for mechanical processing and mass production, and can meet the requirements of harsh working conditions of armored vehicles.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to the field of vehicle tire processing, and particularly discloses a compression molding method of a long fiber composite material loading wheel for a vehicle tire, which comprises the following steps: broadening a continuous fiber bundle, impregnating the continuous fiber bundle in a resin liquid, drying and pressing the continuous fiber bundle into a prepreg, the continuous fiber bundles are selected from any one of carbon fiber bundles and glass fiber bundles; the resin liquid is prepared by hot melting of resin, and the resin is any one of polyether-ether-ketone resin, polyphenylene sulfide resin, polyaryletherketone resin, polyimide resin and maleic anhydride resin; cutting the prepreg, laying the cut prepreg in a mold, carrying out pre-forming treatment and material arrangement, then carrying out heating and pressurizing treatment, and carrying out pressure maintaining, cooling and demolding to obtain a blank wheel; the blank wheel is subjected to flash cutting treatment to obtain a finished loading wheel; the material has the advantages of high strength, good toughness and difficulty in layering.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of vehicle tire processing, and more specifically, to a compression molding method for a long fiber composite material road wheel for a vehicle tire. Background Art

[0002] Road wheels and track rollers are important components of the running part of tracked vehicles. At present, the road wheels and track rollers of tracked armored vehicles at home and abroad are made of steel and aluminum alloy. Due to the high density of metal, the road wheels and track rollers are heavy, and the lightweighting is affected to a certain extent. In particular, various accessories of unmanned armored vehicles are in urgent need of lightweighting.

[0003] Although composite road wheels designed with existing process technology are light in weight, most of the base materials are processed by epoxy resin liquid laying technology, which has low production efficiency, complex manufacturing process, poor product precision, and cannot be machined. In addition, the bonding force between fiber layers is weak, and it is very easy to delaminate, fluff and break. The product quality cannot be guaranteed, and it is difficult to achieve mass production. The mechanical properties cannot meet the requirements of the harsh working conditions of armored vehicles.

[0004] Therefore, it is a problem to be solved to prepare a new vehicle tire road wheel which has the advantages of high strength, good toughness, and not easy to delaminate, is suitable for mechanical processing and mass production, and can meet the use under harsh working conditions of armored vehicles. Summary of the invention

[0005] In order to prepare a new vehicle tire road wheel with the advantages of high strength, good toughness, and not easy to delaminate, suitable for mechanical processing and mass production, and able to meet the use of armored vehicles under harsh working conditions, the present application provides a molding method for a long fiber composite material road wheel for a vehicle tire.

[0006] The present application provides a compression molding method for a long fiber composite material road wheel for a vehicle tire, which adopts the following technical solution: A compression molding method for a long fiber composite material road wheel for a vehicle tire comprises the following steps: S1. After widening the continuous fiber bundle, impregnating it with a resin liquid, wherein the continuous fiber bundle accounts for 35-65% of the weight of the resin liquid, and the impregnation is dried and pressed into a prepreg; the continuous fiber bundle is selected from any one of a carbon fiber bundle and a glass fiber bundle; the resin liquid is obtained by hot melting a resin, and the resin is any one of a polyetheretherketone resin, a polyphenylene sulfide resin, a polyaryletherketone resin, a polyimide resin, and a maleic anhydride resin; S2, after the prepreg is cut, it is evenly laid layer by layer in the forming mold, and the temperature is raised to pre-forming under the conditions of temperature 150-180°C and pressure 10-20MPa. After the material is evenly heated, it is heated to 230-400°C, and heated at a pressure of 30-45MPa for 120-180min, and then the prepreg is pressure-maintained, cooled, and demolded to obtain a blank wheel; S3. The blank wheel is processed by cutting the flash edge to obtain the finished road wheel.

[0007] Preferably, the prepreg is any one of polyetheretherketone prepreg, polyphenylene sulfide prepreg, polyaryletherketone prepreg, polyimide prepreg and maleic anhydride prepreg.

[0008] By adopting the above technical scheme, the reinforcing effect of reinforcing fibers and resin liquid is utilized to make the road wheels prepared by prepreg have the advantages of high strength and high toughness; and in the molding process, first preforming is carried out at 150-180°C to ensure that the prepreg is evenly dispersed in the mold while ensuring the molding effect of the prepreg, and then the temperature is increased for further molding treatment, and heating is carried out under high pressure conditions for a long time to ensure uniform molding of the multi-layer prepreg in the molding mold, and the bonding compatibility between the prepreg layers is high, and the problems of poor interlayer bonding force and layer peeling are not prone to occur, so that the road wheels have the advantages of high strength, good toughness, and are not prone to delamination, are suitable for mechanical processing and mass production, and can meet the use of armored vehicles under harsh working conditions.

[0009] Preferably, the carbon fiber bundle is a modified carbon fiber bundle, and the modified carbon fiber bundle is prepared by the following method: The carbon fiber bundle is subjected to laser etching to obtain an etched carbon fiber bundle, which is then dispersed in a triethanolamine solution, and then the etched carbon fiber bundle is filtered out to obtain a loaded carbon fiber bundle, which is dispersed in a boric acid solution, and then the loaded carbon fiber bundle is filtered out, subjected to a heating treatment, and cooled and dispersed to obtain a modified carbon fiber bundle.

[0010] By adopting the above technical scheme, the surface roughness of the carbon fiber bundle is increased after laser etching. The etched carbon fiber bundle is dispersed in a triethanolamine solution, so that the triethanolamine is dispersed and adhered to the surface of the carbon fiber bundle, and then contacted with boric acid. The amino group in the triethanolamine is used to facilitate the combination with the hydroxyl group of the boric acid in the boric acid solution. In the process of preparing the road wheel, the triethanolamine and boric acid on the surface of the carbon fiber bundle are cross-linked, which improves the surface roughness of the carbon fiber bundle while improving the connection effect between the carbon fiber bundle and other components in the resin liquid, thereby improving the strength of the road wheel.

[0011] Triethanolamine and boric acid are interspersed on the surface of the carbon fiber bundle. The addition of nitrogen in triethanolamine and the filling of boron in boric acid can further improve the flexibility of the carbon fiber bundle filaments, so that the carbon fiber bundle filaments have high strength and high flexibility. The filaments of the modified carbon fiber bundle are added to the resin liquid, which not only makes the road wheel have high strength but also high toughness. At the same time, in the process of hot pressing to prepare the road wheel, the bonding and composite effect of the modified carbon fiber bundle is used between the layers of the prepreg to further improve the stability of each layer of the road wheel, and it is not easy to have stratification problems, thereby ensuring the quality of the road wheel.

[0012] Preferably, the triethanolamine solution is prepared from a triethanolamine aqueous solution and polyethylene glycol 1000 in a mass ratio of 1:0.01-0.02.

[0013] By adopting the above technical scheme, the lubricating effect of polyethylene glycol 1000 is utilized to reduce the viscosity of the triethanolamine solution, so as to ensure that the carbon fiber bundles are evenly dispersed in the triethanolamine solution. The amino groups in triethanolamine and the hydroxyl groups in polyethylene glycol are utilized to further promote the formation of a cross-linked network in the process of preparing the prepreg. The hydroxyl groups in boric acid are combined to improve the density and stability of the cross-linked network on the surface of the carbon fiber bundle, and a cross-linked network with good flexibility is formed on the surface of the carbon fiber bundle filaments. While increasing the contact area between the carbon fiber bundle and the components in the resin liquid, the carbon fiber bundle filaments have good flexibility, can achieve multiple bending and folding in the mold, and ensure the molding effect of the road wheel. The contact area between the carbon fiber bundle filaments and the resin liquid is large, so that the carbon fiber bundles in the resin liquid are stably dispersed, and the strength and toughness of the prepreg are further improved. At the same time, the delamination problem is not easy to occur during the prepreg processing, so as to ensure the processing quality of the road wheel.

[0014] Preferably, the polyphenylene sulfide resin comprises the following raw materials in parts by weight: 80-100 parts of polyphenylene sulfide resin particles, 1-3 parts of polyethylenediamine-modified microcrystalline cellulose, 1-2 parts of plasticizer, 0.5-1 parts of lubricant, 0.5-1 parts of antioxidant, and 1-2 parts of rosin acid ester.

[0015] By adopting the above technical scheme, the polyethylenediamine and rosin acid ester in the polyethylenediamine-modified microcrystalline cellulose are conveniently intercalated between the polyphenylene sulfide molecular chains to increase the distance between the molecules, thereby increasing the flexibility of the molecular chains, and cooperating with the filling effect and adsorption effect of the microcrystalline cellulose to further improve the strength of the prepreg formed by the polyphenylene sulfide resin; and the double bonds in the rosin acid ester are convenient to cooperate with the polyphenylene sulfide resin particles, thereby improving the mechanical strength and impact resistance of the prepreg prepared by the polyphenylene sulfide resin, and the carboxyl groups in the rosin acid ester are convenient to cooperate with the polyethylenediamine-modified microcrystalline cellulose, thereby further improving the crosslinking density of the polyphenylene sulfide resin, thereby further improving the strength and flexibility of the prepreg.

[0016] Polyethylenediamine-modified microcrystalline cellulose, rosin acid ester and lubricant are matched together. The amino group of polyethylenediamine is used to facilitate the connection with the sulfide bond in the polyphenylene sulfide molecular chain, reducing the friction between polyphenylene sulfide molecules, thereby increasing the lubrication effect. The ester group in the rosin acid ester is combined to further reduce the friction between polyphenylene sulfide molecules and improve the lubrication effect of the prepreg. Combined with the lubricant, not only the road wheel has a better molding effect, but also the road wheel has a higher quality.

[0017] Preferably, the polyethylenediamine-modified microcrystalline cellulose is prepared from a polyethylenediamine solution and microcrystalline cellulose in a mass ratio of 1:2-6.

[0018] By adopting the above technical scheme, the polyethylenediamine solution utilizes its bonding effect to adhere to the surface of the microcrystalline cellulose, and utilizes the connecting effect of polyethylenediamine and polyphenylene sulfide to improve the stability of the microcrystalline cellulose in the prepreg. Combined with the filling effect of the microcrystalline cellulose, the toughness and strength of the road wheel prepared from the prepreg are further improved.

[0019] Preferably, the plasticizer consists of hexanediol ester and ethylene phthalate in a mass ratio of 1:0.5-1.

[0020] By adopting the above technical scheme, hexanediol ester and ethylene phthalate are combined to plasticize polyphenylene sulfide by utilizing their good plasticizing effect, and the resin processing and molding temperature is reduced. At the same time, the ester group in the hexanediol ester molecule is connected with the sulfide bond in the polyphenylene sulfide resin to further improve the compatibility and ensure that the prepreg has high flexibility and strength.

[0021] Preferably, the lubricant is composed of fatty alcohol polyoxyethylene ether and oleic acid amide in a mass ratio of 1:0.5-1.

[0022] By adopting the above technical scheme, fatty alcohol polyoxyethylene ether and oleic acid amide are matched, and the ether bond of fatty alcohol polyoxyethylene ether is matched with the ether bond of polyphenylene sulfide, so as to further increase the flexibility of the road wheel, reduce the intermolecular force of polyphenylene sulfide, and improve the lubrication effect of the road wheel; and the amide group in oleic acid amide can react with the sulfide bond of polyphenylene sulfide, so that oleic acid amide is adsorbed on the surface of polyphenylene sulfide to form a lubricating layer, reduce the friction coefficient, and improve the lubrication effect, and cooperate with rosin acid ester and modified carbon fiber bundle, the lubrication effect of the ester group cooperates with the modified carbon fiber bundle to reduce the intermolecular force of polyphenylene sulfide, and further improves the lubrication effect, thereby ensuring the quality of the road wheel.

[0023] Preferably, the pressure holding time is 40-60 minutes.

[0024] By adopting the above technical solution, the pressure holding time is limited to ensure that the road wheel has high strength and good surface smoothness after molding, and is not prone to shrinkage and cracking problems.

[0025] In summary, this application has the following beneficial effects: 1. The reinforcing effect of reinforcing fiber and resin liquid is utilized to make the road wheel prepared by prepreg have the advantages of high strength and high toughness; and in the molding process, first preforming is carried out at 150-180℃ to ensure that the prepreg is evenly dispersed in the mold and the molding effect of the prepreg is ensured, and then the temperature is increased for further molding treatment, and heating is carried out under high pressure for a long time to ensure that the multi-layer prepreg is evenly molded in the molding mold. In addition, the bonding compatibility between the prepreg layers is high, and the problems of poor interlayer bonding force and layer peeling are not likely to occur. The road wheel has the advantages of high strength, good toughness, and is not prone to stratification. It is suitable for mechanical processing and mass production, and can meet the use of armored vehicles under harsh working conditions.

[0026] 2. Triethanolamine and boric acid are interspersed on the surface of the carbon fiber bundle. The addition of nitrogen in triethanolamine and the filling of boron in boric acid can further improve the flexibility of the carbon fiber bundle filaments, so that the carbon fiber bundle filaments have high strength and high flexibility. The filaments of the modified carbon fiber bundle are added to the resin liquid, which not only makes the road wheel have high strength but also high toughness. At the same time, in the process of hot pressing to prepare the road wheel, the bonding and composite effect of the modified carbon fiber bundle is used between the layers of the prepreg to further improve the stability of each layer of the road wheel, and it is not easy to have stratification problems, thereby ensuring the quality of the road wheel.

[0027] 3. Polyethylenediamine-modified microcrystalline cellulose, rosin acid ester and lubricant are matched. The amino group of polyethylenediamine is used to facilitate the connection with the sulfide bond in the polyphenylene sulfide molecular chain, reducing the friction between polyphenylene sulfide molecules, thereby increasing the lubrication effect. The ester group in the rosin acid ester is combined to further reduce the friction between polyphenylene sulfide molecules and improve the lubrication effect of the prepreg. Combined with the lubricant, not only the road wheel has a better molding effect, but also the road wheel has a higher quality. DETAILED DESCRIPTION

[0028] The present application is further described in detail below with reference to the embodiments.

[0029] Preparation example of modified carbon fiber bundle: The following raw materials are all commercially available.

[0030] Preparation Example 1: The modified carbon fiber bundle is prepared by the following method: Add triethanolamine to water and stir until the triethanolamine is completely dissolved to obtain a 5% triethanolamine aqueous solution, add 0.15 kg of polyethylene glycol 1000 to 10 kg of the triethanolamine aqueous solution, and stir until the polyethylene glycol 1000 is completely dissolved to obtain a triethanolamine solution; After the carbon fiber bundle is treated with laser etching, the average porosity of the carbon fiber bundle after laser etching is 35%, and an etched carbon fiber bundle is obtained. 5kg of the etched carbon fiber bundle is added to 50kg of triethanolamine solution, immersed and stirred at a speed of 120r / min for 30min, and the etched carbon fiber bundle is filtered and separated to obtain a loaded carbon fiber bundle; 5kg of the loaded carbon fiber bundle is placed in 50kg of boric acid solution, and the boric acid solution is a 5% boric acid aqueous solution. The boric acid solution is immersed and stirred at a speed of 120r / min for 30min, and then the loaded carbon fiber bundle is filtered out, heated to 280℃ for 30min, cooled to room temperature, and dispersed until the loaded carbon fiber bundles do not stick to each other and agglomerate, to obtain a modified carbon fiber bundle.

[0031] Preparation Example 2: This preparation example differs from Preparation Example 1 in that: 0.1 kg of polyethylene glycol 1000 was added to 10 kg of the triethanolamine aqueous solution, and the mixture was stirred until the polyethylene glycol 1000 was completely dissolved to obtain a triethanolamine solution.

[0032] Preparation Example 3: This preparation example differs from Preparation Example 1 in that: 0.2 kg of polyethylene glycol 1000 was added to 10 kg of the triethanolamine aqueous solution, and the mixture was stirred until the polyethylene glycol 1000 was completely dissolved to obtain a triethanolamine solution.

[0033] Preparation example of polyphenylene sulfide resin: The following raw materials are all commercially available.

[0034] Preparation Example 4: Polyphenylene sulfide resin is prepared by the following method: The polyethylenediamine was placed in water and stirred until the polyethylenediamine was completely dissolved to obtain a polyethylenediamine solution with a concentration of 1%, and 1 kg of the polyethylenediamine solution was evenly sprayed on the surface of 4 kg of microcrystalline cellulose, and the microcrystalline cellulose was dried and dispersed until the microcrystalline cellulose did not stick to each other and agglomerated to obtain polyethylenediamine-modified microcrystalline cellulose; the average particle size of the microcrystalline cellulose was 40 μm; Weigh 90 kg of polyphenylene sulfide resin particles, 2 kg of polyethylenediamine-modified microcrystalline cellulose, 1.4 kg of plasticizer, 0.8 kg of lubricant, 0.8 kg of antioxidant, and 1.4 kg of rosin acid ester, mix and stir evenly, and extrude and granulate at 285 ° C to obtain polyphenylene sulfide resin; the plasticizer consists of hexanediol ester and ethylene phthalate in a mass ratio of 1:1; the lubricant consists of fatty alcohol polyoxyethylene ether and oleic acid amide in a mass ratio of 1:1; the antioxidant is antioxidant 1010.

[0035] Preparation Example 5: This preparation example differs from Preparation Example 4 in that: 1 kg of polyethylenediamine solution is evenly sprayed on the surface of 6 kg of microcrystalline cellulose, and the microcrystalline cellulose is dried and dispersed until the microcrystalline cellulose does not stick to each other and agglomerate, thereby obtaining polyethylenediamine-modified microcrystalline cellulose; Weigh 80 kg of polyphenylene sulfide resin particles, 1 kg of polyethylenediamine-modified microcrystalline cellulose, 1 kg of plasticizer, 0.5 kg of lubricant, 0.5 kg of antioxidant, and 1 kg of rosin acid ester, mix and stir evenly, and extrude and granulate at 285 ° C to obtain polyphenylene sulfide resin; the plasticizer consists of hexanediol ester and ethylene phthalate in a mass ratio of 1:0.5; the lubricant consists of fatty alcohol polyoxyethylene ether and oleic acid amide in a mass ratio of 1:0.5.

[0036] Preparation Example 6: This preparation example differs from Preparation Example 4 in that: 1 kg of polyethylenediamine solution is evenly sprayed on the surface of 2 kg of microcrystalline cellulose, and the microcrystalline cellulose is dried and dispersed until the microcrystalline cellulose does not stick to each other and agglomerate, thereby obtaining polyethylenediamine-modified microcrystalline cellulose; Weigh 100 kg of polyphenylene sulfide resin particles, 3 kg of polyethylenediamine-modified microcrystalline cellulose, 2 kg of plasticizer, 1 kg of lubricant, 1 kg of antioxidant, and 2 kg of rosin acid ester, mix and stir evenly, and extrude and granulate at 285°C to obtain polyphenylene sulfide resin; the plasticizer consists of hexanediol ester and ethylene phthalate in a mass ratio of 1:1; the lubricant consists of fatty alcohol polyoxyethylene ether and oleic acid amide in a mass ratio of 1:1.

[0037] Example

[0038] The following raw materials are all commercially available.

[0039] Embodiment 1: A compression molding method for a long fiber composite material road wheel for a vehicle tire: S1, widening the carbon fiber bundle and impregnating it with a resin liquid, the resin liquid is made by hot melting of polyaryletherketone resin, the carbon fiber bundle accounts for 55% of the weight of the resin liquid, and the impregnation is dried and pressed into a polyaryletherketone prepreg; the polyaryletherketone prepreg is a sheet with an average thickness of 0.2 mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 103% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 5MPa, and the temperature is increased to 150°C at a heating rate of 5°C / min, and then the pressure is increased to 20MPa for preforming. The material in the mold is observed and arranged every 30 minutes, and the temperature is increased to 180°C. After the material is evenly arranged, the preforming mold is removed, and the heating is continued. The pressure is increased to 25MPa, and the temperature is increased to 395°C. It is heated and formed at a pressure of 40MPa for 180min, and then the pressure is maintained for 60min. During the pressure maintenance period, the pressure is kept at 40MPa. Finally, the temperature is cooled at a cooling rate of 20°C / min, and the temperature is cooled to below 60°C. The mold is removed by pressure relief to obtain a rough wheel. S3. The blank is cut and flashed to obtain a finished road wheel.

[0040] Embodiment 2: This embodiment differs from Embodiment 1 in that: S1, widening the carbon fiber bundle and impregnating it with resin liquid, the resin liquid is made by hot melting polyphenylene sulfide resin, the carbon fiber bundle accounts for 45% of the weight of the resin liquid, and the impregnation is dried and pressed into a polyphenylene sulfide prepreg; the polyphenylene sulfide prepreg is a coil with an average thickness of 0.15 mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 104% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 10MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 200°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 30MPa, and the temperature is raised to 320°C. The prepreg is heated and formed at a pressure of 40MPa for 120min, and then the pressure is maintained for 60min. During the pressure maintenance period, the pressure is kept at 40MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min. When the temperature drops below 60°C, the pressure is released and the mold is removed to obtain a rough wheel.

[0041] Embodiment 3: This embodiment differs from Embodiment 1 in that: S1, widening the carbon fiber bundle and impregnating it with a resin liquid, the resin liquid is made by hot melting of polyetheretherketone resin, the carbon fiber bundle accounts for 60% of the weight of the resin liquid, and the impregnation is dried and pressed into a polyetheretherketone prepreg; the polyetheretherketone prepreg is a coil with an average thickness of 0.25 mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 103% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 20MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 200°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 40MPa, and the temperature is raised to 380°C. The prepreg is heated and formed at a pressure of 40MPa for 180min, and then the pressure is maintained for 60min. During the pressure maintenance period, the pressure is kept at 40MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min. When the temperature drops below 60°C, the pressure is released and the mold is removed to obtain a rough wheel.

[0042] Embodiment 4: This embodiment differs from Embodiment 1 in that: S1, widening the carbon fiber bundle and impregnating it with a resin liquid, the resin liquid is made by hot melting of polyimide resin, the carbon fiber bundle accounts for 50% of the weight of the resin liquid, and the impregnation is dried and pressed into a polyimide prepreg; the polyimide prepreg is a sheet with an average thickness of 0.2 mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 105% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 20MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 220°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 30MPa, and the temperature is raised to 400°C. The prepreg is heated and formed at a pressure of 40MPa for 180min, and then the pressure is maintained for 60min. During the pressure maintenance period, the pressure is kept at 40MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min. When the temperature drops below 60°C, the pressure is released and the mold is removed to obtain a rough wheel.

[0043] Embodiment 5: This embodiment differs from Embodiment 1 in that: S1, widening the carbon fiber bundle and impregnating it with resin liquid, the resin liquid is made by hot melting of maleic resin, the carbon fiber bundle accounts for 60% of the weight of the resin liquid, and the impregnation is dried and pressed into a maleic resin prepreg; the maleic resin prepreg is a sheet with an average thickness of 0.25 mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 105% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 20MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 180°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 25MPa, and the temperature is raised to 230°C. The prepreg is heated and formed at a pressure of 35MPa for 130min, and then the pressure is maintained for 40min. During the pressure maintenance period, the pressure remains unchanged at 35MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min, and the temperature is lowered to below 60°C. The mold is released and the rough wheel is obtained.

[0044] Embodiment 6: This embodiment differs from Embodiment 1 in that: S1, widening the carbon fiber bundle and impregnating it with resin liquid, the resin liquid is made by hot melting of polyetheretherketone resin, the carbon fiber bundle accounts for 65% of the weight of the resin liquid, and the impregnation is dried and pressed into polyetheretherketone prepreg; the polyetheretherketone prepreg is a coil with an average thickness of 0.15mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 103% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 10MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 200°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 30MPa, and the temperature is raised to 390°C. The prepreg is heated and formed at a pressure of 45MPa for 120min, and then the pressure is maintained for 40min. During the pressure maintenance period, the pressure is kept at 40MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min, and the temperature is lowered to below 60°C. The mold is released and the rough wheel is obtained.

[0045] Embodiment 7: This embodiment differs from Embodiment 1 in that: S1, widening the glass fiber bundle and impregnating it with resin liquid, the resin liquid is made by hot melting of polyetheretherketone resin, the glass fiber bundle accounts for 35% of the weight of the resin liquid, and the impregnation is dried and pressed into polyetheretherketone prepreg; the polyetheretherketone prepreg is a coil with an average thickness of 0.25mm; S2. The prepreg is cut into a shape that basically matches the road wheel mold, and is laid into the mold layer by layer. The total weight of the prepreg is calculated as 103% of the theoretical weight of the road wheel. After adding the material, the pressure is increased to 10MPa, and the material is heated to 150°C at a heating rate of 5°C / min for preforming. The material in the mold is observed and arranged every 10 minutes, and the temperature is raised to 160°C. After the material is evenly arranged, the preforming mold is removed, and heating is continued. The pressure is increased to 30MPa, and the temperature is raised to 390°C. The prepreg is heated and formed at a pressure of 30MPa for 120min, and then the pressure is maintained for 60min. During the pressure maintenance period, the pressure remains unchanged at 30MPa. Finally, the prepreg is cooled at a cooling rate of 20°C / min, and the temperature is lowered to below 60°C. The mold is released and the rough wheel is obtained.

[0046] Embodiment 8: This embodiment differs from Embodiment 1 in that: The reinforcing fiber is the modified carbon fiber bundle prepared in Preparation Example 1, and the resin liquid is the resin liquid prepared in Preparation Example 4.

[0047] Embodiment 9: This embodiment differs from Embodiment 1 in that: The reinforcing fiber is the modified carbon fiber bundle prepared in Preparation Example 2, and the resin liquid is the resin liquid prepared in Preparation Example 5.

[0048] Embodiment 10: This embodiment differs from Embodiment 1 in that: The reinforcing fiber is the modified carbon fiber bundle prepared in Preparation Example 3, and the resin liquid is the resin liquid prepared in Preparation Example 6.

[0049] Embodiment 11: This embodiment differs from Embodiment 8 in that: No boric acid solution and triethanolamine solution were added during the preparation of the modified carbon fiber bundles.

[0050] Embodiment 12: This embodiment differs from Embodiment 8 in that: No polyethylenediamine-modified microcrystalline cellulose and rosin acid ester were added during the preparation of polyphenylene sulfide resin.

[0051] Embodiment 13: This embodiment differs from Embodiment 8 in that: In the preparation process of polyphenylene sulfide resin, the polyethylenediamine-modified microcrystalline cellulose is replaced by microcrystalline cellulose of equal mass.

[0052] Embodiment 14: This embodiment differs from Embodiment 8 in that: During the preparation of polyphenylene sulfide resin, rosin acid ester is replaced by rosin resin of equal mass.

[0053] Performance testing: 1. Strength detection The road wheels were prepared by the preparation methods of Examples 1 to 14 respectively, and the tensile strength was tested with reference to GB / T1040.1, and the data were recorded.

[0054] 2. Toughness test The road wheels were prepared by the preparation methods of Examples 1-2 and 8-13, respectively. The impact strength was tested with reference to GB / T1843. A high notched impact strength indicated good toughness. The data were recorded.

[0055] 3. Stability test The road wheels were prepared by the preparation methods of Examples 1-12 and 14, and their delamination phenomenon was scored, with 10 points for no delamination phenomenon → 0 points for severe delamination and complete separation and splitting between layers; and their surface smoothness was scored, with 10 points for smooth and complete → 0 points for rough surface with cracks and pits. The higher the smoothness, the better the lubrication molding effect.

[0056] Table 1 Performance test table (“ / ” in the table means that the corresponding embodiment did not test the item, so there is no data) project Tensile strength (MPa) <![CDATA[Impact strength (kJ / m 2 ).]]> Stratification score (points) Smoothing score (points) Example 1 210.6 7.2 10 10 Example 2 185.4 8.0 10 10 Example 3 218.2 / 9 / Example 4 214.8 / 10 / Example 5 138.5 / 9 / Example 6 220.1 / 9 / Example 7 172.9 / 10 / Example 8 224.3 8.7 10 / Example 9 223.7 8.8 10 / Example 10 224.8 8.6 10 / Embodiment 11 217.6 8.1 8 8.5 Example 12 215.9 8.3 / 6 Embodiment 13 221.0 8.5 / / Embodiment 14 223.5 / / 8 It can be seen from Examples 1-7 and Table 1 that the road wheels prepared in the present application have high strength and good toughness, are not easy to delaminate, have good stability, have high surface smoothness, and have good compression molding effects and high quality.

[0057] It can be seen from Example 1 and Examples 8-10 and Table 1 that the modified carbon fiber bundle and the prepared polyphenylene sulfide resin are combined to improve the strength and toughness of the road wheel through triethanolamine and boric acid on the surface of the modified carbon fiber bundle, and polyethylenediamine-modified microcrystalline cellulose and rosin acid ester and plasticizer in the polyphenylene sulfide resin.

[0058] It can be seen from Example 8 and Examples 11-14 and Table 1 that no boric acid solution and triethanolamine solution were added during the preparation of the modified carbon fiber bundle in Example 11, which is compared with Example 8. This shows that the loading of boric acid solution and triethanolamine on the surface of the carbon fiber bundle can not only improve the bonding compatibility between the modified carbon fiber bundle and the polyphenylene sulfide resin, making it less prone to delamination problems, but also improve the flexibility of the carbon fiber bundle filaments and the toughness of the finished road wheel. At the same time, the connection effect of the boric acid solution and triethanolamine can form a stable connection network with the polyphenylene sulfide resin, thereby improving the strength of the road wheel.

[0059] In Example 12, no polyethylenediamine-modified microcrystalline cellulose and rosin acid ester were added during the preparation of the polyphenylene sulfide resin. Compared with Example 8, it is shown that the filling effect of polyethylenediamine-modified microcrystalline cellulose and rosin acid ester can further improve the strength and toughness of the road wheel, and the lubricating effect can improve the surface smoothness of the road wheel.

[0060] In Example 13, during the preparation of polyphenylene sulfide resin, an equal amount of microcrystalline cellulose is used to replace the polyethylenediamine-modified microcrystalline cellulose. Compared with Example 8, the presence of polyethylenediamine can not only improve the connection effect between the polyphenylene sulfide resin and the modified carbon fiber bundle, but also be intercalated between the polyphenylene sulfide molecules to further improve the toughness and strength of the road wheel.

[0061] In the preparation process of polyphenylene sulfide resin in Example 14, rosin resin of equal mass is used to replace rosin acid ester. Compared with Example 8, it is shown that rosin resin has a certain bonding effect, which is easy to affect the demolding effect of the road wheel, and affects the friction effect and intermolecular force between polyphenylene sulfide molecules, while rosin acid ester can reduce the intermolecular force, ensuring the molding effect of the road wheel while ensuring the strength of the road wheel.

[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A compression molding method for a long fiber composite material road wheel for a vehicle tire, characterized in that: The steps include: S1. After widening the continuous fiber bundle, impregnating it with a resin liquid, wherein the continuous fiber bundle accounts for 35-65% of the weight of the resin liquid, and the impregnation is dried and pressed into a prepreg; the continuous fiber bundle is selected from any one of a carbon fiber bundle and a glass fiber bundle; the resin liquid is obtained by hot melting a resin, and the resin is any one of a polyetheretherketone resin, a polyphenylene sulfide resin, a polyaryletherketone resin, a polyimide resin, and a maleic anhydride resin; S2, after the prepreg is cut, it is evenly laid layer by layer in the forming mold, and the temperature is raised to pre-forming under the conditions of temperature 150-180°C and pressure 10-20MPa. After the material is evenly heated, it is heated to 230-400°C, and heated at a pressure of 30-45MPa for 120-180min, and then the prepreg is pressure-maintained, cooled, and demolded to obtain a blank wheel; S3. The blank wheel is processed by cutting the flash edge to obtain the finished road wheel.

2. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 1, characterized in that: The prepreg is any one of polyetheretherketone prepreg, polyphenylene sulfide prepreg, polyaryletherketone prepreg, polyimide prepreg and maleic anhydride prepreg.

3. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 1, characterized in that: The carbon fiber bundle is a modified carbon fiber bundle, and the modified carbon fiber bundle is prepared by the following method: The carbon fiber bundle is subjected to laser etching to obtain an etched carbon fiber bundle, which is then dispersed in a triethanolamine solution, and then the etched carbon fiber bundle is filtered out to obtain a loaded carbon fiber bundle, which is dispersed in a boric acid solution, and then the loaded carbon fiber bundle is filtered out, subjected to a heating treatment, and cooled and dispersed to obtain a modified carbon fiber bundle.

4. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 3, characterized in that: The triethanolamine solution is prepared from a triethanolamine aqueous solution and polyethylene glycol 1000 in a mass ratio of 1:0.01-0.

02.

5. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 1, characterized in that: The polyphenylene sulfide resin comprises the following raw materials in parts by weight: 80-100 parts of polyphenylene sulfide resin particles, 1-3 parts of polyethylenediamine-modified microcrystalline cellulose, 1-2 parts of plasticizer, 0.5-1 parts of lubricant, 0.5-1 parts of antioxidant, and 1-2 parts of rosin acid ester.

6. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 5, characterized in that: The polyethylenediamine-modified microcrystalline cellulose is prepared from a polyethylenediamine solution and microcrystalline cellulose in a mass ratio of 1:2-6.

7. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 5, characterized in that: The plasticizer is composed of hexanediol ester and ethylene phthalate in a mass ratio of 1:0.5-1.

8. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 5, characterized in that: The lubricant consists of fatty alcohol polyoxyethylene ether and oleic acid amide in a mass ratio of 1:0.5-1.

9. The compression molding method of a long fiber composite material road wheel for a vehicle tire according to claim 1, characterized in that: The pressure holding time is 40-60 minutes.

Citation Information

Patent Citations

  • Resin prepreg fiber sheet composite material production method

    CN103507280A

  • Carbon fiber surface treatment method and application

    CN108560243A

  • Prepreg and carbon-fiber-reinforced composite material

    CN112041380A

  • Environment-friendly nanofiber material capable of rapidly adsorbing heavy metal ions and preparation method thereof

    CN112844313A

  • Forming method for composite material radome

    CN113927920A